Malaria and hemoglobin S: resistance or protection? - Maritza Margarita Cabrera Zamora (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Malaria is an infectious disease caused by parasites of the Plasmodium family and transmitted by the female Anopheles mosquitoes. In the year 2015, it ias calculated that there were 212 million new cases and 420 000 deaths. The African region continues bearing the greatest number of cases with an estimate of 90% and the 92% of deaths due to this disease. Many years have passed since the first reports which related the genetic disorder characterized by the presence of hemoglobin S and malaria infection, presuming that there was a resistance to the development of this of infection and it resulting damage. What was controversial about this statement at those times supported the multiple posterior research. The most recent discoveries have allowed a clearer vision of this relationship and new motivations aimed at deepening in the study of this topic. The objective of this work is precisely to analyze the mentioned relationship according to the most recent studies.